Hierarkie Lembaga Negara Di Indonesia - Ahmad Rayhan; Qotrun Nida (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2021)
ABSTRACT:Post-Reform and Amendment to the 1945 Constitution of the Republic of Indonesia in 1998-2002, gave rise to various new things in the legal and constitutional system in Indonesia, one of which is the change in State Institutions in Indonesia, the biggest change is the change in the People's Consultative Assembly which was originally an Institution. Highest State Institutions become Higher State Institutions and the emergence of New State Institutions. Therefore, this study aims to determine the meaning of state institutions and the terms of state institutions in the constitutional system in Indonesia, as well as how the classification and hierarchy of state institutions in Indonesia. The research method used in this research is Normative Juridical. The results showed that State Institutions, State Bodies and State Organs have similarities in terms of language and terms, namely organs that have certain functions in exercising power or state functions. The three terms have been used interchangeably in the Indonesian constitutional system, either in the Constitution or in other regulations. The two State Institutions can be classified based on the legal basis that underlies them, the function of the institution and their position. Meanwhile, based on the hierarchy of State Institutions, it is divided into two levels, namely the central level and the regional level, however the hierarchy does not always discuss which institution is higher and lower, as long as the State Institution is based on the 1945 Constitution and experiences disputes, then in the handling of disputes between State Institutions can be resolved through the authority of the Constitutional Court. Keyword: State Institutions, Hierarchy, classification